Kontroversi Pencatatan Pernikahan Seluruh Agama Serta Kaitannya Dengan Eksistensi Kantor Urusan Agama Di Indonesia - Ivan Tanoto; Andini Zelikho; Yudi Daryadi; Diana Farid; Muhammad Husni Abdulah Pakarti (Yayasan Cendekia Gagayunan Indonesia, 2025)
Marriage registration is a form of state service to protect the public from problems that arise because of marriage ties, such as inheritance rights, maintenance and other civil rights. In fact, the registration of marriages has been regulated in Government Regulation No. 9 of 1975 (PP No. 9/1975) which states that registration of marriages for Islamic religions is recorded by the Religious Affairs Office (KUA) and registration of marriages for non-Islamic religions is carried out by registration officers at the Office. Civil Registry (KCS). However, in early 2024 the Minister of Religion plans to make KUA services inclusive for all religions in Indonesia. In fact, the unification of these services will certainly take away the existence of the KUA as a place to carry out some of the duties of the district and city Department of Religion offices in the field of Islamic religious affairs in sub-district areas as stated in Minister of Religion Decree No. 517 of 2021 concerning the KUA Organization. This research discusses comprehensively the registration of marriages of all religions and its relation to the existence of the KUA in Indonesia. The aim of this research is to determine the impact of the law and controversy over the registration of marriages of all religions at the KUA. The research method we use is normative juridical through a statutory regulatory approach and a conceptual approach. The results of this research indicate that it will be necessary to systematically rework many regulations to make the KUA the centralization of marriage registration for all religions.